Hunted or Scavenged Neanderthals? Taphonomic Approach to Hominin Fossils with Carnivore Damage. (17th May 2017) - Camarós, E.; Cueto, M.; Rosell, J.; Díez, J. C.; Blasco, R.; Duhig, C.; Darlas, A.; Harvati, K.; Jordá, J.; Montes, L.; Villaverde, V.; Rivals, F.
Abstract: Carnivore damage on Neanderthal fossils is a much more common taphonomic modification than previously thought. Its presence could have different explanations, including predatory attacks or scavenging scenarios, which are both situations with important implications concerning Neanderthal behaviour. In the present paper, we analyse several Neanderthal hominin fossils from a taphonomic and forensic perspective in order to infer the nature of the modifications observed on the bone surfaces. Fossils displaying carnivore modifications from Spain, Germany, Belgium and Greece are evaluated from a taphonomic perspective for the first time in a significant sample of hominin specimens. Our results show that the materials analysed have been modified by small to large carnivores and that both attacks and strictly carnivore scavenging events can be inferred. This study also points out the importance of developing taphonomic approaches to the analysis of hominin bone surfaces, which can contribute significantly to knowledge of several aspects of Neanderthal behaviour. Copyright © 2017 John Wiley & Sons, Ltd.